Lithium Trithiocarbonate as a Dual‐Function Electrode Material for High‐Performance Lithium–Sulfur Batteries. Issue 22 (22nd April 2022) - Sul, Hyunki; Bhargav, Amruth; Manthiram, Arumugam
Abstract: The development of practical lithium–sulfur (Li–S) batteries with prolonged cycle life and high Coulombic efficiency is limited by both parasitic reactions from dissolved polysulfides and mossy lithium deposition. To address these challenges, here lithium trithiocarbonate (Li2 CS3 )‐coated lithium sulfide (Li2 S) is employed as a dual‐function cathode material to improve the cycling performance of Li–S batteries. Interestingly, at the cathode, Li2 CS3 forms an oligomer‐structured layer on the surface to suppress polysulfide shuttle. The presence of Li2 CS3 alters the conventional sulfur reaction pathway, which is supported by material characterization and density functional theory calculation. At the anode, a stable in situ solid electrolyte interphase layer with a lower Li‐ion diffusion barrier is formed on the Li‐metal surface to engender enhanced lithium plating/stripping performance upon cycling. Consequently, the obtained anode‐free full cells with Li2 CS3 exhibit a superior capacity retention of 51% over 125 cycles, whereas conventional Li2 S cells retain only 26%. This study demonstrates that Li2 CS3 inclusion is an efficient strategy for designing high‐energy‐density Li–S batteries with extended cycle life. Abstract : Implementing Li2 CS3 ‐coated Li2 S (Li2 CS3 @Li2 S) as a cathode material offers desirable cyclic stability, enabled by a suppressed polysulfide shuttling and stable solid electrolyte interphase formation on the anode surface. The unique reaction mechanism of Li2 CS3 alters the conventional Li–S reaction pathway to increase the discharge voltage.